2017
DOI: 10.3389/fphys.2017.00942
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Tissue Growth by the Mammalian Hippo Signaling Pathway

Abstract: The integrative control of diverse biological processes such as proliferation, differentiation, apoptosis and metabolism is essential to maintain cellular and tissue homeostasis. Disruption of these underlie the development of many disease states including cancer and diabetes, as well as many of the complications that arise as a consequence of aging. These biological outputs are governed by many cellular signaling networks that function independently, and in concert, to convert changes in hormonal, mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 151 publications
(224 reference statements)
1
30
0
Order By: Relevance
“…It was demonstrated that S100A1 inactivated the Hippo signaling pathway. YAP, the downstream effector of Hippo signaling, is frequently overexpressed in various types of human cancer ( 30 ). The present study found that the depletion of S100A1 reduced total and nuclear YAP protein, and decreased TEAD luciferase reporter activity, serving as a marker of YAP downstream function ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that S100A1 inactivated the Hippo signaling pathway. YAP, the downstream effector of Hippo signaling, is frequently overexpressed in various types of human cancer ( 30 ). The present study found that the depletion of S100A1 reduced total and nuclear YAP protein, and decreased TEAD luciferase reporter activity, serving as a marker of YAP downstream function ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the extracellular soluble regulators of YAP were barely known, until Yu et al found bioactive lipids, LPA, and sphingosine-1-phosphate (S1P) as extracellular regulators of YAP in mammary cell lines [ 37 ]. In addition, several hormones have been proved to regulate YAP, such as epinephrine, estrogen, and glucagon [ 38 ]. In the present study, we demonstrated that propofol acted as another extracellular soluble regulator of YAP.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of mechanobiology, the Hippo pathway has been described to be relevant in regulating tissue growth and organ size [74,75]. The main function of the Hippo pathway is to inhibit Yes-associated proiein (YAP) and Tafazzin (TAZ) transcription co-activators, thereby regulating cell proliferation, apoptosis, and stemness in response to extracellular and intracellular signals, among which cell-cell contact, cell polarity, mechanical cues, ligands of G-protein coupled receptors and cellular energy status [75].…”
Section: Src and The Mechanotransductionmentioning
confidence: 99%